Fluorescence determination of cochineal in strawberry jam in the presence of carmoisine as a quencher by means of four-way PARAFAC decomposition. (30th August 2019) - Rubio, L.; Sanllorente, S.; Sarabia, L.A.; Ortiz, M.C.
Highlights: Determination of cochineal in strawberry jam by EEM and four-way PARAFAC model. Carmoisine acted as a quencher in the fluorescence signal of cochineal. Four-way PARAFAC avoids false compliant decisions in the determination of cochineal. Cochineal was unequivocally identified and quantified in the presence of carmoisine. Cochineal was detected in the strawberry jam above its maximum residue level. Abstract: The determination of cochineal (E-120) in strawberry jam was carried out in the presence of carmoisine (E-122) using the four-way PARAFAC decomposition and excitation-emission fluorescence matrices. In the measured conditions, there was no fluorescence signal for carmoisine due to a strong quenching effect and this colorant also led to a decrease of the fluorescence signal of cochineal. The European Union has fixed a maximum residue level, MRL, for cochineal in jam (100 mg kg −1 ). Therefore, the addition of other food colorant (carmoisine) in the jam could lead to false compliant decisions. The four-way PARAFAC decomposition avoided false compliant decisions caused by the quenching effect. Cochineal was unequivocally identified. Detection capability (CCβ) was 0.72 mg L −1 for probabilities of false positive and false negative fixed at 0.05. Cochineal was detected in the jam (104.63 mg kg −1 ) above the MRL. This amount was compared with the one obtained using a HPLC/DAD method.